Instructional strategies in teaching Chinese as a foreign language of listening-speaking class: a qualitative study - Muchen, Li; Jafri, Nuraini; Muhamad, Mohd Mokhtar; Guo, Wanran (Macrothink Institute, 2024)
Recent advances in language teaching emphasize the integration of listening-speaking skills, reflecting the need for holistic instructional approaches. This paper investigates contemporary teaching methods that synergize these skills, addressing a gap in existing research that often isolates individual teaching strategies. Focusing on instructional techniques, the study aims to enhance communicative competence among language learners, particularly benefiting pre-service lecturers. Utilizing a qualitative methodology, the research employs semi-structured interviews to gather insights into lecturers' pedagogical practices. Thematic analysis, facilitated by ATLAS.ti 24, is used to interpret the data. Key findings reveal that fostering student engagement and motivation, enhancing communicative and inclusive learning, and implementing real-world oriented teaching strategies are effective in integrating listening-speaking in Chinese language education for international students. These insights significantly contribute to the field of language education by advocating for innovative teaching techniques and suggesting future research directions regarding their long-term impact and integration into curricula. This study offers valuable implications for enhancing language learning outcomes).